2021
DOI: 10.1159/000513749
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal History of Allergic Features with Preterm Pregnancy Outcomes in the Japan Environment and Children’s Study

Abstract: Introduction: Previous studies have reported that maternal asthma increases the risk of preterm birth. We hypothesized that inflammatory reactions caused by allergic diseases might affect the uterine environment and, subsequently, perinatal outcomes. The objective of this study was to examine the associations between allergic features among mothers and preterm pregnancy outcomes in a nationwide birth cohort. Methods: We analyzed data from pregnant women obtained from the Japanese Environment and Children’s Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…6 In addition, they found a maternal history of allergic conjunctivitis and AD decreased the risk of early PTB and late PTB, respectively. 6 During pregnancy, immunological deviation, a shift from T-helper (Th) cell type 1-dominated to Th2-dominated immune responses was found to prevent fetal rejection. [8][9][10] Allergic disease is also Th2-biased, and IgE is an alternative marker for Th2-biased immune responses.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…6 In addition, they found a maternal history of allergic conjunctivitis and AD decreased the risk of early PTB and late PTB, respectively. 6 During pregnancy, immunological deviation, a shift from T-helper (Th) cell type 1-dominated to Th2-dominated immune responses was found to prevent fetal rejection. [8][9][10] Allergic disease is also Th2-biased, and IgE is an alternative marker for Th2-biased immune responses.…”
mentioning
confidence: 98%
“…Previous studies showed that maternal BA was associated with an increased risk of adverse obstetric outcomes, including preterm birth (PTB) 4 . However, associations between other maternal allergic diseases, including AD and AR, and adverse obstetric outcomes have rarely been reported 5,6 . Saito et al .…”
mentioning
confidence: 99%
See 3 more Smart Citations